ISLAMIC BRAND PADA PRODUK WARDAH - Dwi Andayani; Wika Islaqul Aisiyah; Yulianti Khoirun Nisa; Abi Tri Ihwan (LPPM INSTITUT AGAMA ISLAM HASANUDDIN PARE, 2024)
This research aims to explore the Islamic values attached to the wardah brand in the Sharia Economy in Indonesia. The theories used are branding and Islamic Branding. Islamic Branding is part of Islamic values in which it combines with the concept of branding through various theoretical approaches based on the principles of religiosity, sharia principles, halal products with Islamic attributes that will differentiate from general products that have been in the past. Brands are also often a tool to help consumers make decisions. In addition, the brand is able to attract consumer interest in using the product.